Applications of nanomaterials in agricultural production - Yali Zhang; Sang Lv; Haoyu Wang; Mingxing Tu; Zhumei Xi; Xianhang Wang (Fruit Research)
Nanotechnology has been widely applied in the field of agriculture to meet the requirements of green agricultural development. In agricultural production applications, nanomaterials have been applied as nano-fertilizers, nano-pesticides, and nano-sensors. This article provides a detailed review of recent agricultural applications of nanomaterials. It will also focus on specific agricultural applications, such as transgenics, product preservation, stress resistance, and growth and development. Finally, the challenges of applying nanomaterials for agricultural research are summarized, and solutions are proposed to promote the safe and efficient utilization of nanomaterials in agricultural production to achieve sustainable agricultural development.